A Devastating Complication of Vivax Malaria: Acute Kidney Injury and Gangrene Feet - Naqvi, Rubina; Siddique, Hania; Taqvi, Syeda Shireen (Pakistan Journal of Kidney Diseases, 2021)
Malarial infestation is common in Pakistan and Plasmodium vivax is a common causative organism. Although it has been managed successfully with usual antimalarials and complications are rare, yet occasionally severe complications are observed including Acute kidney injury. We present her a case of AKI secondary to plasmodium vivax along with gangrene of bilateral feet.